The Thought Remolding Campaign of the Chinese Communist Party-state - Hu Ping; Williams, Philip F.; Wu, Yenna (transl.); Williams, Philip F.; Wu, Yenna (transl.) (Amsterdam University Press, 2012)
In its comprehensive analysis of a wide range of primary and secondary sources in both Chinese and Western languages, this authoritative work stands as the definitive study of the theory, implementation and legacy of the Chinese Communist Party's thought-remolding campaign. This decades-long campaign involved the extraction of confessions from millions of Chinese citizens suspected of heterodoxy or disobedience to party dictates, along with their subjection to various forms of "re-education" and indoctrination. Hu Ping's carefully structured overview provides a valuable insider's perspective, and supersedes the previous landmark study on this vastly interesting topic.
Deze studie gaat in op de theorie, uitvoering en nalatenschap van de propagandacampagne van de Chinese Communistische Partij. Deze decennialange campagne bestond onder andere uit het ondervragen van miljoenen burgers die verdacht werden van andersdenkendheid of ongehoorzaamheid. Deze zorgvuldig gestructureerde verhandeling overstijgt de klassieke studie Thought Reform and the Psychology of Totalism (1969) van Robert jay Lifton. In tegenstelling tot het werk van Lifton, hanteert Hu Pings studie een eigentijds postcommunistisch perspectief en is het verrijkt met ervaringen van Chinezen die direct gevolgen hebben ondervonden van de maoïstische propagandacampagne.
English
Keywords: China; History; Postwar 20th century history, from c 1945 to c 2000; Society & culture: general; Politics & government; Marxism & Communism; Political structures: totalitarianism & dictatorship; Political oppression & persecution; geschiedenis; political science; china; communistische partij; politicologie; history; geography; and auxiliary disciplines; Authoritarianism; Intelligentsia; Mao Zedong